Information security for professional counseling in organization - Mohamed, Abdikadir Yusuf; Abubaka, Yusree; Ibrahim, Jamaludin (Research Publish Journals, 2016)
An Information Security Consultant (ISC) provides subject matter expertise and analysis to First Info Tech clients. The role of the ISC is to bridge the gap between high level security policies, requirements and technical/operational implementation of those requirements. Information security is a never ending game where the playing field consists of computer networks, servers, software applications, users, and data. The information security consultant is the coach with a job of helping organizations (team) balance two separate balls. One ball is ease of access, storing, and transmitting data. The other ball is ensuring information confidentiality, availability, and integrity. In this paper we will discuss much about information security consultant service and we will also highlight information security policy, security awareness, security certified, professional security organization and the business canvas model for information security consultant.